PELAGIC ENVIRONMENT IN THE WESTERN PART OF JAKARTA BAY - Nontji, Anugerah; Supangat, Imam (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Seven stations in the western part of Jakarta Bay were occupied monthly from June 1974 to June 1975. Monthly variations of several hydrological and biological properties of the pelagic environments are described. Rainfall over the hinterland of Jakarta plays important role in lowering the salinity in the bay. On the other hand the phosphate content is more closely associated with the rainfall over Jakarta. The main source of phosphate is likely to come from the result of urban activities in Jakarta. There is a fair corespondence in annual fluctuation between phosphate and phytoplankton chlorophyll. Annual mean of properties at each station shows that from the shore outward the values of phosphate, phytoplankton chlorophyll, and zooplankton volume decreased while of salinity and transparency increased. Interrelationships among several factors are discussed.